Introducing innovation into an ESP program: Aviation English for cadets - Kırkgöz, Yasemin; ER, MUSTAFA (My University, 2018)
The aim of English for Specific Teaching (ESP) in Turkish universities is to support the development of scientific literacy in learners' field of specialism in English. Implicit in this objective is to make the ESP curriculum tailor-made to meet the learners' specific needs. In this study, we describe evaluating the new Turkish Air Force Academy (TurAFA) curriculum, which has been in use for some time. TurAFA is unique in that it aims to train cadets to become combat pilots leading Turkish Air Force. After contextualizing our research, we provide an evaluation of an innovative "Aviation English for Cadets" (AEC) curriculum which has beendesigned to fulfill cadets' individual and institutional needs. AEC is based on a comprehensive needs analysis involving all stakeholders including the graduates, field experts, instructors and cadets. The most innovative aspect of the curriculum is the introduction of virtual aviation, a challenging innovation in the curriculum for cadets. We illustrate the course content with a simulated flight snapshot. Finally, we discuss the curriculum evaluation in relation to its professional relevance, use of technology, and challenges encountered in the curriculum development process. The study illustrates a localized practice; yet, we believe that it has implications for EAP/ESP practitioners and researchers globally.
Keywords: Aviation English; Curriculum Development and Evaluation; Higher Education